Export Promotion Bureau, Bangladesh
The Bangladesh Export Promotion Bureau is the government body responsible for promoting, regulating, and monitoring trade, investments and exports from Bangladesh. The website information on Bangladesh includes trading and investment opportunities, export and import policies, economic situation of the country, statistics and data on exports, contact information, list of chambers of commerce and industry, export processing zones, and other related organizations.